The Effects of Tax Complexity and Tax Fairness on Tax Compliance - MEINARNI ASNAWI (The Indonesian Journal of Accounting Research, 2013)
This study aims to provide empirical evidence that tax complexityand tax fairness affect tax compliance. This study is conductedusing the experimental method, which is designed to have a post-testcontrol group to observe behavioral changes in tax compliancedecisions.This experimental method uses 173 participants from a vocationalcollege, which is a part of the Faculty of Economics and Business,Universitas Gadjah Mada, the Master of Economics faculty at theUniversitas Cenderawasih Jayapura and participants from a trainingcourse in local finance run by the PSKD UGM. The participants arecategorized into two groups, they are group A (the experimental group)and group B (the control group).The result of this study shows that taxcomplexity negatively correlates to tax compliance in the control group,and positively correlates in the experimental group. Tax complexity positivelycorrelates with tax fairness in both the control group and theexperimental group. Tax fairness shows a significant and positive correlationwith tax compliance in both the control group and the experimentalgroup. Tax fairness mediates the relationship between tax complexityand tax compliance.Tax compliance is a psychological factorthat essentially contributes to enhancing tax compliance. Tax complexityshows indications of noncompliance unless it is subjected to tax fairness,when it indicates tax compliance. The tax institutions should provideappropriate explanations related to the taxation system, so the taxpayerscould understand the complexities of the taxation system.